THE CALCULATION OF THE OUTREACH RATE OF SHARIA COOPERATIVES ON THE POOR SOCIETY IN EAST JAVA - Tita Novita Sari; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to analyze the outreach of sharia cooperatives in East Java. This study uses a quantitative approach using Tobit regression analysis techniques. Sampling using a purposive sampling technique and obtained 8 Islamic cooperatives that fit the criteria. The results of this study indicate that sharia cooperatives are in reaching poor people in East Java. Sharia cooperatives that have the highest coverage scores are BMT Mandiri Artha Syariah and BMT Al-Izzah Amanah Umat.Keywords: Sharia Cooperatives, outreach, BMTREFFERENCE Ali, Hasan. (2003). Berbagai macam transaksi dalam islam (fiqih muamalah). Jakarta: Raja Grafindo Persada.Badan Pusat Statistik Jakarta Pusat. (2018). statistik Indonesia tahun 2018. Jakarta: Badan Pusat Statistik.Burhanuddin. (2013). Koperasi syariah dan pengaturannya di Indonesia. Malang: UIN-Maliki Press.Henock, M. S. (2018). Financial sustainability and outreach performance of saving and credit cooperatives: The case of Eastern Ethiopia. Asia Pacific Management Review, 24(1), 1-9. https://doi.org/10.1016/j.apmrv.2018.08.001Hermes, N., Lensink, R., & Meesters, A. (2011). Outreach and efficiency of microfinance institutions. World Development, 39(6), 938–948. DOI: 10.2139/ssrn.1143925Mulyaningsih, Y., Nuryartono, N., Oktaviani, R., & Firdausy, C. M. (2017). Analisis jangkauan (outreach) LKMS bagi rumah tangga miskin sektor pertanian di perdesaan Bogor, Jawa Barat. Jurnal Ilmu Pertanian Indonesia, 20(3), 182–190.Soemitra, A. (2018). Peran Pemberdayaan Masyarakat oleh Lembaga Keuangan Mikro Syariah dalam Perspektif Sustainable Development Goals (SDGs). Skripsi tidak diterbitkan. Medan: Fakultas Ekonomi dan Bisnis Islam UIN Sumatera Utara.USAID. (2006). Evaluating MFI's social performance: A measurement tool. The United States Agency for International Development.Qardhawi, Yusuf. (2005). Spektrum zakat dalam membangun ekonomi kerakyatan. Jakarta : ZikrulWorld Bank. (2018). Poverty and shared prosperity 2018: Piecing together the poverty puzzle. Washington DC: World Bank.